The effect of water exercise in treating the sacral angle that causes pain in the lumbar region for the lower back 35-45 years old (Journal of the College of Basic Education, 2022)
The research aims to prepare water exercises compatible with the possibility of the research sample. And to know the effect of water exercise on the degree of pain. And to know the effect of water exercise on the strength of the back muscles. And to know the effect of water exercise on the flexibility of the trunk. The researcher used the experimental method to suit the research problem. The research community was composed of (18) women attending the Rehabilitation Center for Physiotherapy and Joint Diseases in Baghdad, the chest canal area, who suffer from lower back pain after examination and diagnosis. (35-45) years old. After conducting the tests and processing the data by statistical means, the researcher concluded the following results: Water exercises affected (sacral angle, degree of pain) and the improvement was evident in the post-tests. It was found that water exercise has a clear effect on raising health fitness in both (strength and flexibility). Water exercises helped treat lower back pain